Analysis of Experimental Physics Publications for Teaching Over the Past Decade (2015-2024) - Muddasir, Fadhil; Hun, Hilarius Donatus; Jubaedah; Sorpay, Yeheskel; Widayani; Triyanta (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
Physics experiments play a crucial role in fostering student engagement, serving as a foundation for active learning and critical skill development. Experiments provide hands-on experiences that help students develop problem-solving abilities, scientific reasoning, and collaborative skills. Understanding the trends in experimental physics publications for teaching is essential to assess how this field evolves and to identify research gaps. This study examines the publication trends of experimental physics research for teaching over the past decade (2015–2024) by analyzing 2352 articles from prominent journals, including Physics Education, The Physics Teacher, European Journal of Physics, and American Journal of Physics. The results highlight notable peaks in publication during key periods, such as the COVID-19 pandemic, which accelerated innovation in virtual and remote experimental setups. Mechanics emerged as the most frequently researched topic, while thermodynamics and modern physics were underrepresented, suggesting significant research gaps. The analysis also identifies the transformative potential of technological advancements like smartphone-based tools and augmented reality, which have significantly enhanced teaching methodologies. This study underscores the need for collaborative efforts among researchers, educators, and policymakers to develop accessible, scalable, and innovative experimental approaches.